2023
DOI: 10.1021/acscatal.3c01101
|View full text |Cite
|
Sign up to set email alerts
|

Polarization Manipulation of NiO Nanosheets Engineered with Fe/Pt Single Atoms for High-Performance Electrocatalytic Overall Alkaline Seawater Splitting

Abstract: Regulating the metal–support interaction is recognized as an effective approach to modulating the electronic structure of single-atom catalysts. Here, we put forward a strategy to modulate the anchored metallic single atoms by manipulating the surface polarization of the support, which is demonstrated to be effective in designing alkaline seawater electrocatalysts. Specifically, we introduce Mn doping in weak-polarized NiO nanosheets to modulate its surface polarization and thereby regulate the electronic meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(8 citation statements)
references
References 66 publications
0
6
0
Order By: Relevance
“…For advanced HER catalysts, it is traditionally observed that the primary choice among the electrochemical community revolves around utilizing Pt. [76][77][78] However, there has been a joint effort to delve into cost-effective alternative sources that are abundantly available. Table 2 shows a comparison of the performance of the-state-of-art HER cathode catalysts, evaluated in direct seawater electrolysis.…”
Section: Her Electrocatalysts For Seawater Electrolysismentioning
confidence: 99%
“…For advanced HER catalysts, it is traditionally observed that the primary choice among the electrochemical community revolves around utilizing Pt. [76][77][78] However, there has been a joint effort to delve into cost-effective alternative sources that are abundantly available. Table 2 shows a comparison of the performance of the-state-of-art HER cathode catalysts, evaluated in direct seawater electrolysis.…”
Section: Her Electrocatalysts For Seawater Electrolysismentioning
confidence: 99%
“…In multiphase catalysts, various interesting structures often appear when metals are loaded on support leading to significant changes in catalytic activity and stability, which has received much attention from researchers. 124,132–139 With the rise of nanomaterials research, strong metal–support interaction (SMSI) was formally introduced in the 1970s. 140 The noble metal loaded on TiO 2 is reduced at 200 °C followed by uniform dispersion on the support.…”
Section: Innovative Strategies To Improve Oer Performancesmentioning
confidence: 99%
“…[5][6][7][8] By loading a decorating metal onto catalyst support and supported metal particles, the support might induce significant electronic perturbations of the supported metal particles, denoted as electronic metal-support interactions (EMSIs), which can modulate the d-band centers of the metal, leading to excellent catalytic performance. [9][10][11][12] However, undesigned metal modification often fails to significantly promote catalytic activity in a wide variety of catalytic systems, and the modification effect needs to be further studied under realistic reaction conditions. Therefore, it is significant and challenging to design well-defined metal-modified catalysts with excellent catalytic performance for heterogeneous catalytic reactions.…”
Section: Introductionmentioning
confidence: 99%